Upaya pembentukan warga negara yang baik dan tantangan yang dihadapi oleh para guru PKn peserta SM3T 2015 - Suyato, Suyato; Murdiono, Mukhamad; Mulyono, Budi; Arpannudin, Iqbal (Universitas Negeri Yogyakarta, 2016)
The research was an explorative research deploying interview and questionnaire as collecting data methods. Collected data was analyzed descriptive qualitatively. The research found that (1) although respondents have different conceptions of good citizens, they have shared view on main features of good citizen, namely caring others, responsibility, independence, democratic, critical, and simple life; (2) almost all of them have chosen lecturing as instructional method to develop good citizen; (3) they have found both internal and external obstacles in dealing with their efforts, such as teachers themselves and students and the lack of infrastructures of schools; and (4) many efforts were deployed, one of them was of seduction their colleagues to work professionally. They believed that it was not thought but caught by which a good citizen could be developed. They were ready to be examples.